Estimates of phenotypic and genetic parameters on lifetime performance traits in Murrah buffaloes - DUTT, TRIVENI; TANEJA, V K (The Indian Journal of Animal Sciences, 2013)
Analysis of performance records of 1 647 Murrah huffaloes revealed that the farms and years significantly influenced the lifetime traits. The least-square means for number of lactations completed.productive herd life, lifetime milk yield and milk yield per day of productive herd life were 5.78±0.15 and 2 401±63 days and 9 993±338 and 4.00±0.07 kg respectively. The corresponding heritability estimates of these traits were 0.17±0.07, 0.17±0.07, 0.26±0.08 and 0.26±0.08. The phenotypic and genetic correlationsof lifetime milk yield with number of lactation. completed and productive herd life were close to 1 and were higher than those of milk yield per day of productive herd hle with longevity traits.